“La mia signora mi dice che io sono brava donna…”. Storia di una migrante bulgara, tra relazioni di assistenza e pratiche di cura - Eugenio Zito (Narrare i Gruppi, 2017)
In this paper I report a Bulgarian female migrant caregiver’s “life-story”, especially focusing on her relation with an old Italian woman, and the care practices performed in her favor in Italy, and on her daughter and parents still living in Bulgaria. I chose to do it by means of an anthropological approach based on experience as field of mediation between personal dimensions and historical and social processes and therefore centered on the body conceived as historical product, the influence of political and social forces on shaping human lives, and finally interested in the specific link between bodies and work. From this analysis, based on language and narratives, I think useful cultural aspects may emerge about “gender” and care practices, regarding the two women linked by an assistance relationship, and the activities/strategies used by the Bulgarian caregiver to fulfill her family obligations.